Growing burden of diabetes in sub- saharan Africa: contribution of pesticides ? - (:unkn) unknown (My University, 2013)
The diabetes burden is growing in Sub-Saharan Africa (SSA). The low overall access to health care has been documented to contribute to the high diabetes-related mortality. Due to economic, demographic, epidemiological and nutrition transitions in SSA, the growing prevalence of diabetes appears to be related to obesogenic lifestyles and the intergenerational impact of malnutrition in women of childbearing age. Both overnutrition and undernutrition have been associated with the development of diabetes and other chronic diseases. Africans are also suspected of being genetically predisposed to diabetes. According to existing data in developed countries, exposure to pesticides, particularly organochlorines and metabolites, is associated with a higher risk of developing type 2 diabetes and its comorbidities. In African countries, pesticide exposure levels often appear much higher than in developed countries. Furthermore, undernutrition, which is still highly prevalent in SSA, could increase susceptibility to the adverse effects of organic pollutants. Therefore, the growing and inadequate use of pesticides may well represent an additional risk factor for diabetes in SSA. Additionally, high exposure to pesticides in African infants in utero and during the perinatal period may increase the intergenerational risk of developing diabetes in SSA.
Keywords: African Research